JWST’s First View of Tidal Disruption Events: Compact, Accretion-driven Emission Lines and Strong Silicate Emission in an Infrared-selected Sample - Megan Masterson; Kishalay De; Christos Panagiotou; Erin Kara; Wenbin Lu; Anna-Christina Eilers; Muryel Guolo; Armin Rest; Claudio Ricci; Sjoert van Velzen (The Astrophysical Journal Letters, 2025)
Mid-infrared (MIR) emission from tidal disruption events (TDEs) is a powerful probe of the circumnuclear environment around dormant supermassive black holes. This emission arises from the reprocessing of intrinsic emission into thermal MIR emission by circumnuclear dust. While the majority of optical- and X-ray-selected TDEs show only weak dust echoes consistent with primarily unobscured sight lines, there have been growing efforts aimed at finding TDEs in obscured environments using MIR selection methods. In this work, we present the first JWST observations of four MIR-selected TDEs with the JWST Mid-Infrared Instrument (MIRI) Medium-Resolution Spectrometer (MRS). Two of these sources show flares in other wavelength bands (one in optical, one in X-ray), while the other two are MIR-only transients. None of these TDEs showed pre-outburst nuclear activity, but all of the MIRI/MRS observations reveal emission lines associated with highly ionized gas in the nucleus, implying ionization from TDE accretion. Additionally, all four sources show silicate emission features around 10 and 18 μ m that are much stronger than the features seen in active galactic nuclei. We suggest that the emitting dust is optically thin to its own emission and show that the MIR spectrum is consistent with emission from optically thin dust in the nucleus. All four sources show an excess at short wavelengths ( λ  < 8 μ m), which could arise from a late-time plateau in the intrinsic flare, akin to what is seen in late-time UV observations of unobscured TDEs, although self-consistent dust modeling is required to fully assess the strength of this late-time plateau.